Performance of grid connected photovoltaic inverter with maximum power point tracker and power factor control - Mekhilef, Saad; Ahmed, M.E.; Younis, M.A.A. (2008)
Detailed analysis, simulation and hardware results of grid connected inverter with maximum power point tracker and power factor control in Malaysian climate are presented. A six-switch topology inverter with symmetrical Pulse Width Modulation (PWM) switching technique is used. A low pass filter is incorporated in the circuit to filter out unwanted harmonics and produce a sinusoidal AC current. Low total harmonic current distortion at the inverter output can be achieved. The three-phase PWM switching pattern was developed using Xilinx FPGA. The developed system is also capable of adjusting the power factor to unity. A 3kVA power transformer with a 1:2 ratio is constructed to provide galvanic isolation for better circuit performance and circuit protection. Hardware results for proposed solar photovoltaic inverter configuration interconnected to the grid are also presented. From the experimental results it is confirmed that the harmonic distortion of the inverter output waveform is within the limits laid down by the utility companies.